Modified Fagerstrom Tolerance Questionnaire (Adolescents) Indonesian Version: Validity and Reliability Study - Gusti Ayu Kade Widya Aryanti; I Ketut Andika Priastana (Universitas Triatma Mulya, 2019)
Introduction. Smoking has become a special concern in the world. Dependence on cigarettes can endanger almost every organ in the body and reduce the health of smokers in general. Research that proposes the identification of smoking behavior has been carried out, but only a few have focused on testing the validity and reliability of the instrument for measuring the level of smoking dependence. This study examines the validity and reliability of the Modified Fagerstrom Tolerance Questionnaire (Adolescents) in Indonesian Version. Methods. Respondents in this study were 30 teenage smokers. The statistical test used is the Pearson Product-Moment Correlation test. Results. Modified Fagerstrom Tolerance Questionnaire (Adolescents) consists of 7 questions that are used to measure the level of smoking dependence and show results in the Corrected Item-Total Correlation section, all questions have a positive value and r count ≥ r table (0.361). The Reliability Statistics table gets the Cronbach's Alpha result is 0.892 with 7 items. Conclusion. Modified Fagerstrom Tolerance Questionnaire (Adolescents) Indonesian Version declared valid and reliable for use in assessing smoking dependence on Indonesian adolescents.